The fungi - Watkinson, Sarah C.; Boddy, Lynne; Money, Nicholas P. (Waltham, MA, USA Elsevier, Academic Press, 2016)
Offers a comprehensive and thoroughly integrated treatment of the biology of the fungi. This modern synthesis highlights the scientific foundations that continue to inform mycologists today, as well as recent breakthroughs and the formidable challenges in current research. The Fungi combines a wide scope with the depth of inquiry and clarity offered by three leading fungal biologists. The book describes the evolution and astonishing diversity of the fungi, their genetics and complex life cycles, and intriguing mechanisms of spore release. The distinctive cell biology of the fungi is linked to their development as well as their metabolism and physiology. Fungi interact with plants and animals and are major players in global nutrient cycles. Plants and animals are supported by mutualistic relationships with fungi, damaged by pathogenic species, and their dead tissues are recycled by saprotrophic fungi. This book is written for undergraduates and graduate students, and is also useful for professional biologists interested in specific topics in fungal biology.
1 Fungal diversity / Nicholas P. Money : Evolutionary origins of the fungi and their relationships to other eukaryotes -- The classification of fungi -- Fungal phyla -- Microsporidia -- Miscellaneous microorganisms studied by mycologists -- Further reading -- Weblinks. 2 Fungal cell biology and development / Nicholas P. Money : Organelles, cells, organs -- Cell structure -- Growth and cell division -- The mycelium -- Multicellular organs -- Further reading -- Weblink. 3 Spore production, discharge, and dispersal / Nicholas P. Money : Diversity, development, and functions of spores -- Spore size and shape -- Spore discharge -- Dispersal of spores and aeromycology -- Dispersal of spores by animals -- Aquatic spores -- Further reading. 4 Genetics: variation, sexuality, and evolution : Defining individuals, populations, and species -- Life cycles and the sexual process -- Variation, microevolution, and speciation -- Further reading. 5 Physiology and adaptation / Sarah C. Watkinson : Introduction -- Nutrient acquisition, uptake, and assimilation -- Secondary metabolism -- Sensing and responding to the environment -- Developmental adaptation for nutrient acquisition -- Geomycology -- Further reading and references. 6 Molecular ecology / Sarah C. Watkinson : The application of DNA technology in the ecology of fungi -- Fungal diversity in the environment -- Linking fungal diversity and ecosystem processes -- Whole-genome sequencing and comparative genomics -- Further reading. 7 Mutualistic symbiosis between fungi and autotrophs / Sarah C. Watkinson : Mycorrhiza -- Lichens -- Endophytes -- Further reading -- Journal articles and reviews. 8 Pathogens of autotrophs / Lynne Boddy : Spectrum of interactions of fungi with plants -- Distribution of pathogens amongst fungal groups -- Susceptibility to and defence against fungal pathogens -- Key events in the disease cycle of pathogens -- Case studies -- Development of disease in natural ecosystems and crops -- Diseases of other autotrophs: lichens and seaweeds -- Emerging diseases and the biosecurity threat -- Further reading. 9 Interactions with humans and other animals / Lynne Boddy : Fungi and humans: medical mycology -- Pathogens of other vertebrates -- Killers of invertebrates -- Fungi as food and habitat for animals -- Mutualistic associations between fungi and animals -- Further reading. 10 Interactions between fungi and other microbes / Lynne Boddy : Fungal-fungal interactions -- Interactions between fungi and bacteria -- Viruses of fungi -- Interactions between fungi and protists -- Further reading. 11 Fungi, ecosystems, and global change / Lynne Boddy : Introduction -- The roles of fungi in element cycles, bioconversions, and energy flows -- Biodiversity and biogeography of fungi -- Climate change responses of fungi -- Land use change -- Pollution, pesticides, fertilisers, nutrient distribution, and recycling -- Movement of biota -- Fungal conservation -- Further reading. 12 Fungi and biotechnology / Nicholas P. Money : The industrial significance of fungi -- The cultivation of mushrooms for food and pharmaceuticals -- Production of food and drink using yeasts and filamentous fungi -- Fermentation technology -- Genetic manipulation of fungi for biotechnology -- Modern biotechnological applications of filamentous fungi and yeasts -- Further reading. Appendix: glossary of common mycologicla (and related) terms -- Index.
"Academic Press is an imprint of Elsevier."
Previous edition by: Michael J. Carlile, Sarah C. Watkinson, Graham W. Gooday. San Diego, California : Academic Press, 2001.
Includes bibliographical references and index.
Keywords: Fungi